The future for the therapeutics of abdominal aortic aneurysm: engineered nanoparticles drug delivery for abdominal aortic aneurysm - Du, Pengchong; Hou, Yachen; Su, Chang; Gao, Jiamin; Yang, Yu; Zhang, Jinying; Cui, Xiaolin; Tang, Junnan (Frontiers in Bioengineering and Biotechnology, 2024)
Abdominal aortic aneurysm (AAA) is a severe cardiovascular disease with a high mortality rate. Several screening and diagnostic methods have been developed for AAA early diagnosis. Open surgery and endovascular aortic repair (EVAR) are clinically available for patients who meet the indications for surgery. However, for non-surgical patients, limited drugs exist to inhibit or reverse the progression of aneurysms due to the complex pathogenesis and biological structure of AAA, failing to accumulate precisely on the lesion to achieve sufficient concentrations. The recently developed nanotechnology offers a new strategy to address this problem by developing drugcarrying nanoparticles with enhanced water solubility and targeting capacity, prolonged duration, and reduced side effects. Despite the rising popularity, limited literature is available to highlight the progression of the field. Herein, in this review, we first discuss the pathogenesis of AAA, the methods of diagnosis and treatment that have been applied clinically, followed by the review of research progressions of constructing different drug-loaded nanoparticles for AAA treatment using engineered nanoparticles.In addition, the feasibility of extracellular vesicles (EVs) and EVs-based nanotechnology for AAA treatment in recent years are highlighted, together with the future perspective. We hope this review will provide a clear picture for the scientists and clinicians to find a new solution for AAA clinical management.